Why Should I Switch Off: Understanding the Barriers to Sustainable Consumption?. Issue 2 (June 2019) - Malodia, Suresh; Bhatt, Alka Singh
This study identifies the barriers to sustainable consumption and measures the discriminating power of these barriers between groups having significant differences in their energy conservation behaviour. By analysing the response of 321 consumers to questionnaire survey in India, results reveal that belief in material growth is found to be the most important factor associated with the energy conservation behaviour across levels (grey, grey-green and green energy consumers). However, belief in technology is negatively associated with energy conservation efforts to all consumers. However, cynicism does not relate to energy conservation efforts. The results are significant to the agencies designing energy conservation campaigns aimed at modifying energy consumption behaviour of domestic consumers.